Law Enforcement Implementation and Efforts in Protecting Company Ownership Rights Over Rising Disputes over Share Ownership Reviewed Based on Law No. 40/2007 concerning Limited Liability Companies - Jeane Neltje Saly; Qonita Rizqi Iffani Putri (Al Ahkam, 2023)
The primary objective of this study is to explore and identify effective legal measures to safeguard a company's ownership rights and resolve disputes over share ownership. To achieve this, the author employed normative legal research methods to analyze the issue thoroughly. This study specifically focuses on applying and enforcing laws designed to protect the administrators of limited liability companies, as stipulated in law number 30 of 2007 concerning limited liability companies. By examining these legal provisions, the author aims to provide insights into how companies can better protect their ownership rights and prevent conflicts over share ownership.Keywords : legal safeguards, ownership rights, enforcement of laws, normative legal research